Dating systemic financial stress episodes in the EU countries - Thibaut Duprey; Benjamin Klaus; Tuomas Peltonen (Bank of Canada, 2016)
This paper introduces a new methodology to date systemic financial stress events in a transparent, objective and reproducible way. The financial cycle is captured by a monthly country-specific financial stress index. Based on a Markov-switching model, high financial stress regimes are identified, and a simple algorithm is used to select those episodes of financial stress that are associated with a substantial negative impact on the real economy. By applying this framework to 27 European Union countries, the paper is a first attempt to provide a chronology of systemic financial stress episodes in addition to the expert-detected events that are currently available.
Keywords: C54; G01; G15; 330; Central bank research; Econometric and statistical methods; Business fluctuations and cycles; Economic models; Financial markets; Financial stability; Monetary and financial indicators; Financial system regulation and policies